The zero product rule states that

The zero product rule is used to solve quadratic equations when you have factored them. An example is as follows:

The quadratic equation

For example, if `a * b = 0`, then either `a = 0` or `b = 0`.If the product of two or more expressions is zero, then either expression is equal to zero.

The zero product rule is used to solve quadratic equations when you have factored them. An example is as follows:

The quadratic equation

`x^2 + 3x + 2 = 0`is factored into

`(x + 1)(x + 2) = 0`Applying the zero product rule,

either `x + 1 = 0`, then `x = -1`

or `x + 2 = 0`, then `x = -2`Therefore we obtained the solution `x = {-1, -2}` for the quadratic equation `x^2 + 3x + 2 = 0` by using the Zero Product Rule.

## No comments:

## Post a Comment